INTERNALIZING VALUES OF JUSTICE IN MUDHARABAH FINANCING PRACTICES AND MUDHARABAH DEPOSITS - Dyah Ayu Perwitasari; Ahmad Roziq; Agung Budi Sulistiyo (Universitas Pendidikan Ganesha, 2017)
This study aims to explore and analyze the forms of fairness values in the practice of mudharabah financing and mudharabah deposits. This type of research is a type of qualitative research with case study approach. The results of this study indicate that this bank has not fully applied the five elements of justice in the practice of mudharabah financing. Of the five principles, BPRS only runs the two principles of justice, namely the form of prohibition of haram and maysir. In order to fulfill these five principles of justice, should the BPRS Asri Madani Nusantara apply pure mudharabah financing practices, where the profit sharing calculation is done after the project has been realized, the shari'ah education has been intensively to mudharib, the management supervises it intensely on the mudharib-run business, As well as Islamic business ethics that must be owned by human resources banking. While in practice mudharabah deposit, BPRS ASRI Madani Nusantara Jember has applied the five elements of justice that is the form of prohibition of riba, gharar, maysir, dzulm and haram in mudharabah deposit transaction.Keywords: mudharabah, mudharabah deposit, justice